Efektivitas Penurunan COD, BOD dan TSS Limbah Industri Sawit Menggunakan Koagulan Kimia dan Ekstrak Alami Pati Pelepah Sawit - Vera Viena; Bahagia Bahagia; Nurlaini Nurlaini; Rizki Juanda (Fakultas Teknik, 2023)
AbstractRiver water pollution occurs because the disposal of palm oil waste into water bodies that are not managed by factories effectively has affected river pollution in Nagan Raya. The impact has caused the death of fish in the river. The purpose of this study was to analyze the effect of natural coagulant palm frond starch on the treatment of parameters biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS). Palm oil mill Effluents (POME) wastewater samples were taken from the cooling ponds of PT. X in Nagan Raya District and wet palm fronds obtained from community plantations. The POME was pretreated with sedimentation for 24 hours and continued with the Palm natural starch and PAC (Poly Aluminum Chloride) chemical coagulation process. The results showed that the COD test with a contact time of 60 minutes decreased by 19.79%, at contact time of 120 minutes by 48.97% and at contact time of 180 minutes by 74.48%. The results of the BOD test showed that there was a decrease along with a contact time of 60 minutes by 20.48%, a contact time of 120 minutes by 35.30% and a contact time of 180 minutes by 68.08%. The results of the TSS test showed a decrease in TSS with a contact time of 60 minutes by 48.37%, a contact time of 120 minutes by 81.70% and a contact time of 180 minutes by 92.43%.Keywords: palm frond starch, coagulant, sedimentation, palm oil mill effluent (POME)